Dual‐Tube Helmholtz Resonator‐Based Triboelectric Nanogenerator for Highly Efficient Harvesting of Acoustic Energy - Zhao, Hongfa; Xiao, Xiu; Xu, Peng; Zhao, Tiancong; Song, Liguo; Pan, Xinxiang; Mi, Jianchun; Xu, Minyi; Wang, Zhong Lin (Advanced energy materials, 2019)
An acoustic wave is a type of energy that is clean and abundant but almost totally unused because of its very low density. This study investigates a novel dual‐tube Helmholtz resonator‐based triboelectric nanogenerator (HR‐TENG) for highly efficient harvesting of acoustic energy. This HR‐TENG is composed of a Helmholtz resonant cavity, a metal film with evenly distributed acoustic holes, and a dielectric soft film with one side ink‐printed for electrode. Effects of resonant cavity structure, acoustic conditions, and film tension on the HR‐TENG performance are investigated systematically. By coupling the mechanisms of triboelectric nanogenerator and acoustic propagation, a theoretical guideline is provided for improving energy output and broadening the frequency band. Specifically, the present HR‐TENG generates the maximum acoustic sensitivity per unit area of 1.23 VPa−1 cm−2 and the maximum power density per unit sound pressure of 1.82 WPa−1 m−2, which are higher than the best results from the literature by 60 and 20%, respectively. In addition, the HR‐TENG may also serve as a self‐powered acoustic sensor. A dual‐tube Helmholtz resonator‐based triboelectric nanogenerator (HR‐TENG) for highly efficient harvesting of acoustic energy is designed. The present HR‐TENG generates the maximum acoustic sensitivity per unit area of 1.23 VPa−1 cm−2 and the maximum power density per unit sound pressure of 1.82 WPa−1 m−2, which are higher than the best results from the literature by 60 and 20%, respectively.